Epidemiology of injuries in National Collegiate Athletic Association men's tennis: 2014-2015 through 2018-2019 - Robison, H. J.; Boltz, A. J.; Morris, S. N.; Collins, C. L.; Chandran, A. (Journal of Athletic Training, 2021)
Context: The National Collegiate Athletic Association (NCAA) has sponsored men's tennis programs since 1982. The popularity of tennis has grown, as has sponsorship of men's tennis within NCAA institutions. Background: Continued monitoring of athletic injuries is important for identifying emerging temporal patterns. Methods: Exposure and injury data collected in the NCAA Injury Surveillance Program during 2014-2015 through 2018-2019 were analyzed. Injury counts, rates, and proportions were used to describe injury characteristics, and injury rate ratios were used to examine differential injury rates. Results: The overall injury rate was 4.41 per 1000 athlete-exposures. Lateral ligament complex tears of the ankle (8.5%) were the most reported injury. Trunk (15.1%) and shoulder (13.2%) injuries accounted for the largest proportions of all injuries. Noncontact and overuse were the most common mechanisms of injury among all reported injuries, together accounting for 69.4% of all injuries. Conclusions: Findings of this study differed slightly from previous studies, most notably in specific injuries reported. Continued monitoring of specific injury incidence as well as greater participation in injury surveillance is needed to inform the development of nuanced injury prevention strategies for this population.